Phylogeographical patterns of Campanula gr. arvatica, an endemic group of the Cantabrian mountains (NW Iberian Peninsula), based on plastid and nuclear DNA polymorphisms. Issue 5 (3rd July 2020) - Prieto, José Antonio Fernández; Rodríguez, Jose M. Arjona; Sanna, Mauro; Cires, Eduardo
Abstract : Endemicity is a key consideration for conservation, and taxa that are endemic to a single country are vaulable conservation targets. In this study, we investigate endemic species of the genus Campanula in northern Iberian Peninsula based on sequences of nrDNA (internal transcribed spacer, ITS) and plastid regions ( rbcL, trnL-F and trnS-G ) and additionally the secondary structure of ITS2. The main aim of this work was to evaluate the evolutionary history of Campanula gr. arvatica from the Cantabrian Range (northern Iberian Peninsula) and establish phylogeographical patterns. Our results showed that molecular data from nuclear DNA and plastid regions should be applied for management and conservation strategies to monitor this endemic group from northern Spain. Furthermore, molecular evidence indicates significant differences among the three taxa analysed and shows the importance of the Cantabrian Mountains as a refuge for endemic Iberian flora in which processes of neo-speciation and/or crypto-speciation are under way.